Examining Consumers' Recognition of Native and Banner Advertising on News Website Home Pages. Issue 1 (2nd January 2020) - Windels, Kasey; Porter, Lance
Abstract: Native advertising has grown tremendously as consumers have shifted attention from traditional to digital media. Using an eye-tracking method and a general population sample, an online survey examined whether consumers could recognize native ads and banner ads on digital news website home pages with similar speed and effectiveness. It also investigated the relationship between ad skepticism and recognition of native and banner advertising. Results suggest that native ads are more discoverable, or more quickly noticed, than banner ads. However, only 68% of participants could recognize at least one native ad, and those who did took significantly longer to recognize native than banner units as ads. Even among consumers with high skepticism toward advertising, who should have richer knowledge about the strategies and tactics of advertisers, no relationship was found between ad skepticism and native ad recognition.